Curb Cuts and Computers: Advocating for Design Equality in the 1980s. - Petrick, Elizabeth (Design Issues)
This article concerns the history of the curb cut metaphor as applied to personal computer technology in the 1980s. Disability advocates used the metaphor to argue the necessity for accessibility features on computers to enable greater access. To accomplish this goal, these advocates utilized a complex comparison between personal computers and sidewalk ramps to combat assumptions about who the intended computer user was and to argue for how people with different abilities could operate the same technology.